2023
DOI: 10.3389/fnins.2023.1127065
|View full text |Cite
|
Sign up to set email alerts
|

Brain function effects of exercise interventions for cognitive decline: a systematic review and meta-analysis

Diana Karamacoska,
Ali Butt,
Isabella H. K. Leung
et al.

Abstract: IntroductionExercise is recognized as a modifiable lifestyle factor that can mitigate cognitive decline and dementia risk. While the benefits of exercise on cognitive aging have been reported on extensively, neuronal effects in adults experiencing cognitive decline have not been systematically synthesized. The aim of this systematic review was to assess the effects of exercise on cognition and brain function in people with cognitive decline associated with dementia risk.MethodA systematic search was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 87 publications
(271 reference statements)
0
4
0
Order By: Relevance
“…There has been a surprising increase in the significance of exercise as a non-pharmacological therapeutic in the aversion of cognitive decline, enhancement of cognitive function, optimization of daily activities, and clinical improvement in neuropsychiatric symptoms (Huang et al ., 2020 ; Karamacoska et al ., 2023 ; Langoni et al ., 2019 ; Mollinedo Cardalda et al ., 2019 ; Wilke et al ., 2019 ; Xiong et al ., 2021 ). Several observational studies utilizing fMRI technology have indicated that habitual exercise can enhance the functional connectivity of the DMN, as well as improve attention and language networks, in relation to aging-related cognitive decline (Voss et al ., 2010 ; Zlatar et al ., 2013 ).…”
Section: Exercise Influences Brain Healthmentioning
confidence: 99%
“…There has been a surprising increase in the significance of exercise as a non-pharmacological therapeutic in the aversion of cognitive decline, enhancement of cognitive function, optimization of daily activities, and clinical improvement in neuropsychiatric symptoms (Huang et al ., 2020 ; Karamacoska et al ., 2023 ; Langoni et al ., 2019 ; Mollinedo Cardalda et al ., 2019 ; Wilke et al ., 2019 ; Xiong et al ., 2021 ). Several observational studies utilizing fMRI technology have indicated that habitual exercise can enhance the functional connectivity of the DMN, as well as improve attention and language networks, in relation to aging-related cognitive decline (Voss et al ., 2010 ; Zlatar et al ., 2013 ).…”
Section: Exercise Influences Brain Healthmentioning
confidence: 99%
“…The cognitive benefits of exercise are thought to be mediated through increased metabolic activity, improved cerebrovascular function, and enhanced neuroplasticity throughout the brain, especially in highly plastic and sensitive regions like the frontal and temporal lobes. 60 Importantly, different interventions may target specific brain regions; resistance training, for instance, largely benefits executive function. 21 Thus, this analysis examined overall cognition, partly explaining the efficacy of multicomponent exercises.…”
Section: Gradementioning
confidence: 99%
“…The effect of exercise, as well as different programs on activities of daily living in patients with dementia, has been examined to a limited extent [9], with studies indicating that systematic exercise, through various mechanisms, promotes brain function and maintains and improves the cognitive functions [10,28,29].…”
Section: Introductionmentioning
confidence: 99%